2021
DOI: 10.3390/vaccines9050480
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus: Immune Escape and Application of Reverse Genetics in Attenuated Live Vaccine Development

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV), an RNA virus widely prevalent in pigs, results in significant economic losses worldwide. PRRSV can escape from the host immune response in several processes. Vaccines, including modified live vaccines and inactivated vaccines, are the best available countermeasures against PRRSV infection. However, challenges still exist as the vaccines are not able to induce broad protection. The reason lies in several facts, mainly the variability of PRRSV and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 151 publications
0
11
0
Order By: Relevance
“…Seven commercial MLV vaccines are currently used to control and prevent PRRSV infection in China with their corresponding virus strains, including Ingelvac PRRS MLV/RespPRRS MLV (VR-2332), CH-1R (parental strain CH-1a), HuN4-F112 (HuN4), JXA1-P80 (JXA1), R98 (R98), TJM-F92 (TJ), and GDr180 (GD). These PRRS MLV vaccines are obtained from the classical or HP-PRRSV strains, which can provide adequate protection against genetically homologous strains ( Wang et al, 2021 ); however, the protective effect of MLV vaccines for resisting challenge with heterologous strains is far from conclusive. Zhou et al (2017) found that the cross-protective efficacy of three different attenuated vaccine strains (including an HP-PRRSV attenuated vaccine strain) against the NADC30-like strain was extremely limited against infection with the NADC30-like virus.…”
Section: Discussionmentioning
confidence: 99%
“…Seven commercial MLV vaccines are currently used to control and prevent PRRSV infection in China with their corresponding virus strains, including Ingelvac PRRS MLV/RespPRRS MLV (VR-2332), CH-1R (parental strain CH-1a), HuN4-F112 (HuN4), JXA1-P80 (JXA1), R98 (R98), TJM-F92 (TJ), and GDr180 (GD). These PRRS MLV vaccines are obtained from the classical or HP-PRRSV strains, which can provide adequate protection against genetically homologous strains ( Wang et al, 2021 ); however, the protective effect of MLV vaccines for resisting challenge with heterologous strains is far from conclusive. Zhou et al (2017) found that the cross-protective efficacy of three different attenuated vaccine strains (including an HP-PRRSV attenuated vaccine strain) against the NADC30-like strain was extremely limited against infection with the NADC30-like virus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to investigating NA epitopes, there are on-going efforts to identify the largely unknown PRRSV T-cell epitopes [ 51 , 52 , 53 ]. With respect to immunosuppression, PRRSV research is extensive with the predominance of evidence implicating PRRSV suppression/inhibition of type I interferons [ 54 , 55 , 56 ]. Beyond type I interferons, Ma et al reviewed the possible roles of PRRSV to suppress other innate immune defenses: cytokine production, tripartite motif proteins, microRNA, and small ubiquitin-related modifier E3 ligase activity [ 54 ].…”
Section: The Problem Of Prrsvmentioning
confidence: 99%
“…In contrast to MLV vaccines, inactivated PRRSV vaccines are safe and have thus been licensed worldwide. However, several studies have demonstrated that inactivated PRRSV vaccines are ineffective against wild-type infections as they neither trigger the production of specific PRRSV antibodies nor cell-mediated immunity (CMI) responses (Bassaganya-Riera et al, 2004;Kim et al, 2011;Yu et al, 2019;Wang et al, 2021). Li et al evaluated the cross-protective efficacy of the synergy between live-attenuated and inactivated PRRSV vaccines compared with a single vaccination with PRRS modified-live virus (MLV) vaccine against NADC30-like strain.…”
Section: Porcine Reproductive and Respiratory Syndrome Virus Vaccine ...mentioning
confidence: 99%